Force-Activated Isomerization of a Single Molecule - Qi, Jing; Gao, Yixuan; Jia, Haihong; Richter, Marcus; Huang, Li; Cao, Yun; Yang, Huan; Zheng, Qi; Berger, Reinhard; Liu, Junzhi; Lin, Xiao; Lu, Hongliang; et al. (Journal of the American Chemical Society, 2020)
Understanding and controlling isomerization at the single molecular level should provide new insight into the molecular dynamics and design guidelines of functional devices. Scanning tunneling microscopy (STM) has been demonstrated to be a powerful tool to study isomerization of single molecules on a substrate, by either electric field or inelastic electron tunneling mechanisms. A similar molecular isomerization process can in principle be induced by mechanical force; however, relevant study has remained elusive. Here, we demonstrate that isomerization of a N,N-dimethylamino-dianthryl-benzene molecule on Ag(100) can be mechanically driven by the STM tip. The existence of an out-of-plane dimethylamino group in the molecule is found to play a pivotal role in the isomerization process by providing a steric hindrance effect for asymmetric interaction between the STM tip and the molecule. This underlying mechanism is further confirmed by performing molecular dynamics simulations, which show agreement with experimental results. Our work opens the opportunity to manipulate the molecular configuration on the basis of mechanical force.
CRIS-Team Scopus Importer:2023-03-20